Structural analysis of the frontal part of a local car model for crashworthiness - Abdullah, Kassim Abdulrahman; Nimir, Yassin Lutfi Mahmud (OCTA Press, 2013)
For an integral body or a body-on-frame (BOF) vehicle, the vehicle’s frontal part is the major structural subsystem to absorb the impact energy in a frontal vehicle impact. Ideally, for each serious crash situation, the whole available deformation length must be used and all the impact energy must be absorbed without deforming the passenger compartment. It is also important to manage the energy intensity during the crash time because the resulting crash pulse has a large influence on the injury level. Crash simulation softwares are widely used by automotive industry to evaluate occupant risks and injuries. Therefore, the accuracy of the finite element frame model has significant influence on the quality of vehicle impact predictability. This current work aims at building an understanding of structural and design features that can optimize structural integrity in terms of strength, stiffness and crashworthiness of front-part structures. For this purpose, a local car model is selected for analysis so as to study and analyse the crushing behaviour and suggest ways for possible modifications to be made on the structures. Required modifications on the structures are done at the weak zones to enhance crashworthiness of the vehicle. The enhancement processes involve structure’s geometry modifications or implementations of new design features. Concept structure that can improve energy absorption capability while maintaining a permissible deceleration level is presented.